The two of us : a novel - Jones, Andy (Andy P.) (Washington Square Press, 2016)
"A charming, unconventional love story about a couple who embark on a wildly passionate, two-week fling that will change both of their lives forever. If you loved One Day and The Rosie Project, you will fall head-over-heels for The Two of Us. Anyone can fall in love. But not everyone can stay there. Fisher and Ivy have been an item for all of nineteen days. Both of them have been in relationships before, and this time around, they know something is different--they are meant to be together. The fact that they know little else about each other is a minor detail. But over the next year, a time in which their lives are irrevocably altered, Fisher and Ivy discover that falling in love is one thing--and staying there is an entirely different story. The Two of Us is a charming, honest, laugh-out-loud novel about life, love, and the importance of taking neither one for granted"--